2005
DOI: 10.1103/physrevd.72.124021
|View full text |Cite
|
Sign up to set email alerts
|

Nonsupersymmetric attractors

Abstract: We consider theories with gravity, gauge fields and scalars in four-dimensional asymptotically flat space-time. By studying the equations of motion directly we show that the attractor mechanism can work for nonsupersymmetric extremal black holes. Two conditions are sufficient for this, they are conveniently stated in terms of an effective potential involving the scalars and the charges carried by the black hole. Our analysis applies to black holes in theories with N 1 supersymmetry, as well as nonsupersymmetri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
562
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(582 citation statements)
references
References 43 publications
14
562
0
Order By: Relevance
“…where 49) and where Ω b a and P I a are given by 50) together with similar relation for Ω J I and P a I . Using (7.48), we can write down the Maurer-Cartan eqs for the dressed charge.…”
Section: Dressed Chargesmentioning
confidence: 99%
See 1 more Smart Citation
“…where 49) and where Ω b a and P I a are given by 50) together with similar relation for Ω J I and P a I . Using (7.48), we can write down the Maurer-Cartan eqs for the dressed charge.…”
Section: Dressed Chargesmentioning
confidence: 99%
“…Notice by the way that there are different ways to derive the gauge invariant effective scalar potential V ef f of the 6D N = 2 supersymmetric BPS black objects [34,48,49,50].…”
Section: Effective Potential and Attractor Mechanism In 6d And 7dmentioning
confidence: 99%
“…Now, defining for convenience ϕ 0 ≡ 1, we can write 34) and taking into account the normalization at spatial infinity, we find that…”
Section: Extremal Black Holesmentioning
confidence: 99%
“…The entropy, given by eq. (2.41), takes the explicit form 34) and the mass, given by eq. (2.39) becomes…”
Section: Extremal Solutionsmentioning
confidence: 99%
“…In 2005, Sen showed that all extremal black holes, both supersymmetric and non-supersymmetric (non-BPS), exhibit attractor behavior [2]: it is a result of the near-horizon geometry of extremal black holes, rather than supersymmetry. Since then, non-BPS attractors have been a very active field of research (see for instance [3,4,5,6,7,8,9,10,11,12,13,14,15]). In particular, a microstate counting for certain non-BPS black holes was proposed in [16].…”
Section: Introductionmentioning
confidence: 99%